The good doctor. Season four [videorecording (DVD)] - Highmore, Freddie, 1992-; Gonzalez, Nicholas, 1976-; Thomas, Antonia, 1986-; Tomita, Tamlyn; Harper, Hill, 1966-; Schiff, Richard, 1955-; Gubelmann, Fiona, 1980-; Chang, Christina; Pak, Chae-bŏm (Sony Pictures, 2021)
The show is about a young surgeon with autism who is recruited to work at a pediatric unit of a hospital. The hospital is prestigious with many of the toughest cases a surgeon could ever see, but with autism comes clarity that most surgeons will never have. The television series focuses on the relationship between the doctor and patient, and how a man who cannot relate to the people who he tries to help.